An Overview of defected ground structure with practical application of defected ground structure bandpass filter in energy harvester circuit - Khan, M.T. (Maxwell Science Publications, 2014)
The aim of the study is to practically implement the Defected Ground Structure (DGS) based microstrip bandpass filter in an energy harvester circuit. DGS is widely used to bring about an enhancement in the characteristics of microwave circuits. The study of DGS is derived from the concept of Photonic/electromagnetic Band Gap (PBG) structures but it is easier to design and fabricate and has an easier equivalent LC resonator circuit. In this study, DGS has been reviewed from all aspects such as comparing it with PBG, discussing in detail its unit, its structure and property according to various shapes and designs and its several advantages in microstrip filters. Although DGS has various advantages in the area of microwave power amplifier, Wilkinson power divider, microwave antennas, couplers, etc., it is extensively used in the design of microwave filter to achieve stopband effects, slow-wave effects, frequency adjustment etc. Finally a DGS based bandpass filter working at 900 MHz has been designed, fabricated and tested for implementation in an Energy Harvester circuit. Â© Maxwell Scientific Organization, 2014.